Effects of substrate, ant and fungal species on plant fiber degradation in a fungus-gardening ant symbiosis. (April 2017) - DeMilto, Alexandria M.; Rouquette, Monte; Mueller, Ulrich G.; Kellner, Katrin; Seal, Jon N.
Graphical abstract: Highlights: Fiber digestion was quantified in Trachymyrmex fungus-gardening ants. Fiber-rich substrates lost more hemicellulose than fiber-poor substrates. Ant and fungal species influenced hemicellulose but not lignocellulose content of refuse piles. Abstract: Fungus-gardening or attine ants have outsourced most of their digestive function to a symbiotic fungus. The ants feed their fungus – essentially an external digestive organ – a variety of substrates of botanical origin, including fresh and dried flowers, leaves and insect frass (processed leaves). Although plant tissues are rich in fibers (lignocelluloses, hemicelluloses, pectins and starches) and the symbiotic fungus possesses the genetic and enzymatic machinery to metabolize these compounds, the highly derived attines, the leaf-cutters ( Atta and Acromyrmex ), are known to produce fiber-rich waste. While leaf-cutting ants are important consumers of primary plant tissue, there have been fewer studies on physiological activity of fungi grown by closely related ant species in the genus Trachymyrmex, which generally grow related species of fungi, have smaller colonies and consume a wider variety of fungal substrates in addition to fresh leaves and flowers. In this study, we measured the cellulase activity of the fungus-gardening ants Atta texana, Trachymyrmex arizonensis and T. septentrionalis . We then quantified fiber consumption of the fungus-gardening ants Trachymyrmex septentrionalis and Trachymyrmex arizonensis by comparing the amounts and percentages present in their food and in fungus garden refuse during a controlled feeding experiment over the span of several months. Finally, we compared waste composition of T. arizonensis colonies growing different fungal strains, because this species is known to cultivate multiple strains of Leucoagaricus in its native range. The leaf-cutting ant A. texana was found to have lower cellulytic activity than T. arizonensis or T. septentrionalis . Total lignocellulose and hemicellulose amounts were significantly lower in refuse piles than in the substrates fed to the Trachymyrmex colonies, thus these fibers were consumed by the fungal symbionts of these ant species. Although lignocellulose utilization was similar in two distinct fungal species grown by T. arizonensis colonies, hemicellulose utilization was higher in T. arizonensis colonies growing a derived leaf-cutting ant fungal symbiont than when growing a native type of symbiont. The results of this study demonstrate that fiber digestion in fungus-gardening ants is an outcome of ant-fungal interaction.